2023
DOI: 10.1002/pul2.12297
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary hemodynamics and transplant‐free survival in sarcoidosis‐associated pulmonary hypertension: Results from an international registry

Shameek K. Gayen,
Robert P. Baughman,
Steven D. Nathan
et al.

Abstract: Pulmonary hypertension (PH) is a risk factor for mortality in patients with sarcoidosis. Severe PH in chronic lung disease has previously been defined as mean pulmonary arterial pressure (mPAP) ≥ 35 mmHg or mPAP 25 ≥ mmHg with cardiac index (CI) ≤ 2 L/min/m2. However, there is no clear definition denoting severity of sarcoidosis‐associated PH (SAPH). We aimed to determine pulmonary hemodynamic cut‐off values where transplant‐free survival was worse among patients with SAPH. This was a retrospective cohort anal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 20 publications
2
4
0
Order By: Relevance
“…This change in definition results from studies demonstrating that a PVR threshold of 5 WU is a better predictor of mortality in patients with COPD-PH and ILD-PH [ 4 , 6 ]. This finding was also found in patients with sarcoidosis-associated PH [ 5 ]. Severe PH as defined by the 2022 ESC/ERS guidelines was a strong independent predictor of mortality in our cohort of patients, even when accounting for underlying lung disease and lung function.…”
Section: Discussionsupporting
confidence: 67%
See 2 more Smart Citations
“…This change in definition results from studies demonstrating that a PVR threshold of 5 WU is a better predictor of mortality in patients with COPD-PH and ILD-PH [ 4 , 6 ]. This finding was also found in patients with sarcoidosis-associated PH [ 5 ]. Severe PH as defined by the 2022 ESC/ERS guidelines was a strong independent predictor of mortality in our cohort of patients, even when accounting for underlying lung disease and lung function.…”
Section: Discussionsupporting
confidence: 67%
“…Pulmonary hypertension (PH) often accompanies chronic lung diseases such as chronic obstructive pulmonary disease (COPD), idiopathic pulmonary fibrosis (IPF), pulmonary sarcoidosis, and other interstitial lung diseases (ILDs) [ 1 ]. The presence of PH in chronic lung disease portends unfavorable outcomes [ 2 , 3 , 4 , 5 , 6 , 7 ]. Notably, hemodynamic parameters may play a more integral role than lung function in long-term outcomes [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the international registry including unselected patients with SAPH, 115/159 (72.3%) received PAH-targeted therapy, which consisted of monotherapy in 88.2% (PDE5-i: n = 86, ERA: n = 56), bitherapy in 17.6% (PDE5i + ERA: n = 28), and tritherapy in 6.3% (PDE5-I + ERA + prostanoid: n = 10) [45]. In both registries, PAH-targeted therapy was not associated with decreased mortality, provided that treated patients had a significantly worse condition at baseline than the untreated ones [41,45,84].…”
Section: Treatment Of Vascular Disease and Use Of Pah Agentsmentioning
confidence: 98%
“…As far as the definition of severe SAPH goes, with the foreseeable impact of therapeutic measures and timing on LTx evaluation, one study showed that both mPAP ≥ 40 mmHg and PVR ≥ 5 WU were strongly associated with a shorter transplant-free survival and increased risk of death or LTx [84]. Interestingly, and in contrast to common definitions of severe PH in chronic lung diseases, neither a mPAP > 35 mmHg nor mPAP > 25 mmHg with cardiac index ≤ 2 L/min/m 2 were associated with these outcomes.…”
Section: Rhcmentioning
confidence: 99%